The impact of time after radiation treatment on dysphagia in patients with head and neck cancer enrolled in a swallowing therapy program. Issue 3 (10th January 2019) - Van Daele, Douglas J.; Langmore, Susan E.; Krisciunas, Gintas P.; Lazarus, Cathy L.; Pauloski, Barbara R.; McCulloch, Timothy M.; Gramigna, Gary D.; Messing, Barbara P.; Wagner, Cynthia W.; Mott, Sarah L
Abstract: Background: Swallowing dysfunction after radiotherapy (RT) for head and neck cancer can be devastating. A randomized control trial compared swallow exercises versus exercise plus neuromuscular electrical stimulation therapy and found no overall difference in outcomes. Methods: Quality of life (QOL), diet, and swallowing variables collected at discrete intervals on 117 patients were reanalyzed to test the hypothesis that shorter time between the completion of radiotherapy and beginning of the swallowing therapy program yielded improved outcomes. Results: At baseline, subjects < 1 year post radiation had significantly better function than subjects >2 years post RT in several measures. Over the therapy program, the early group showed significant improvement in diet and QOL. Swallowing physiologic variables showed no difference between groups. Conclusion: Beginning a swallowing therapy program within 1 year of completion of radiotherapy demonstrates more consistent improvement in QOL and diet performance compared to later periods.